The Disunity of the Ummah Become 73 Groups in Takhrij Al-Hadith Perspective - Abdul Rohman; Mulyani Mudis Taruna (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2020)
A Hadith states that Muslims will disunity into 73 groups. When the Prophet was still alive all the problems of the Ummah could be returned to him, so there was no disunity. But after he died, many problems surfaced. The event of tahkim (arbitration) as an attempt to resolve the Shiffin war, instead gave rise to three major groups, namely the Shi’ite, Khawarij and Muawwiyah. The last group is often referred to as the ahlus Sunni. These events are often used as legal points, for the emergence of various religious groups in Islam today. The writing of this study uses the study literature method. As for the results of this study concluded, that: a) The Hadith concerning